CATCH-UP vaccines: protocol for a randomized controlled trial using the multiphase optimization strategy (MOST) framework to evaluate education interventions to increase COVID-19 vaccine uptake in Oklahoma - Janitz, Amanda E.; Neil, Jordan M.; Bray, Laura A.; Jervis, Lori L.; Ross, Laura; Campbell, Janis E.; Doescher, Mark P.; Spicer, Paul G.; Williams, Mary L.; Lopez, April K.; Uribe-Frias, Conce A.; Chen, Sixia; et al. (BMC public health, 2023)
Oklahoma's cumulative COVID-19 incidence is higher in rural than urban counties and higher than the overall US incidence. Furthermore, fewer Oklahomans have received at least one COVID-19 vaccine compared to the US average. Our goal is to conduct a randomized controlled trial using the multiphase optimization strategy (MOST) to test multiple educational interventions to improve uptake of COVID-19 vaccination among underserved populations in Oklahoma. Our study uses the preparation and optimization phases of the MOST framework. We conduct focus groups among community partners and community members previously involved in hosting COVID-19 testing events to inform intervention design (preparation). In a randomized clinical trial, we test three interventions to improve vaccination uptake: (1) process improvement (text messages); (2) barrier elicitation and reduction (electronic survey with tailored questions/prompts); and (2) teachable moment messaging (motivational interviewing) in a three-factor fully crossed factorial design (optimization). Because of Oklahoma's higher COVID-19 impact and lower vaccine uptake, identifying community-driven interventions is critical to address vaccine hesitancy. The MOST framework provides an innovative and timely opportunity to efficiently evaluate multiple educational interventions in a single study. ClinicalTrials.gov: NCT05236270, First Posted: February 11, 2022, Last Update Posted: August 31, 2022.